Dosimetric Comparison of Noncoplanar VMAT Without Rotating the Patient Couch Versus Conventional Coplanar/Noncoplanar VMAT for Head and Neck Cancer: First Report of Dynamic Swing Arc - Kouta Hirotaki, MS; Kento Tomizawa, MD, PhD; Satoe Kitou, BS; Shunta Jinno, MS; Shunsuke Moriya, PhD; Takeshi Fujisawa, MD; Sadamoto Zenda, MD, PhD; Takeji Sakae, PhD; Masashi Ito, BS (Advances in Radiation Oncology)
Purpose: This retrospective planning study aimed to verify the usefulness of a clinically available method, dynamic swing arc (DSA), a noncoplanar volumetric modulated arc therapy (VMAT) technique, of the new accelerator OXRAY for head and neck squamous cell carcinoma (HNSCC). We performed dosimetric comparisons between DSA and conventional coplanar/noncoplanar VMAT (C-VMAT/NC-VMAT) plans for HNSCC. Methods and Materials: We selected 32 patients with oropharyngeal and hypopharyngeal cancer treated with C-VMAT at National Cancer Center Hospital East between September 2018 and July 2023. DSA and C/NC-VMAT plans were generated using OXRAY and TrueBeam, respectively. DSA employed noncoplanar 2-arc beams with an O-ring gantry swing, whereas C-VMAT and NC-VMAT used coplanar and noncoplanar 2-arc beams, respectively. Dosimetric parameters, normal tissue complication probability, and delivery times were compared pairwise using the Wilcoxon signed-rank test with Bonferroni correction. Results: For high-risk planning target volume (PTV), D98 values in NC-VMAT plans were closest to the prescribed dose, significantly differing from C-VMAT and DSA plans. DSA plans showed significantly better median conformity and homogeneity indices (0.97 and 7.33, respectively) compared to C-VMAT (0.95 and 8.36) and NC-VMAT (0.96 and 7.96) plans. DSA plans significantly reduced the mean ipsilateral/contralateral parotid gland dose by 5.78/6.93 and 2.88/1.56 Gy (median) compared to C-VMAT and NC-VMAT. NC-VMAT and DSA plans significantly decreased the mean oral cavity dose by 2.16 and 3.22 Gy (median) compared to C-VMAT. DSA plans had the lowest median normal tissue complication for xerostomia with significant differences, followed by NC-VMAT and C-VMAT. The delivery time for DSA plans was longer than VMAT (151 seconds vs 124 seconds), but shorter than NC-VMAT. Conclusions: DSA plans using OXRAY for HNSCC maintained PTV coverage while reducing parotid gland and oral cavity mean doses compared to coplanar VMAT plans, although delivery times increased. DSA plans reduced parotid gland doses and delivery times compared to noncoplanar VMAT plans.